The promise of preschool from Head Start to universal pre-kindergarten - Rose, Elizabeth (Oxford University Press, 2010)
How did the United States move from seeing preschool as a way to give the nation's poorest children a 'head start' to the goal of providing preschool for all children as the beginning of public education? This book investigates how policy choices in the past 45 years helped shape the decisions that policymakers are now making.